2021
DOI: 10.3390/jmse9070762
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Vessel Atmospheric Emissions in the Central Mediterranean over the Last 10 Years and during the COVID-19 Outbreak

Abstract: Giordan Lighthouse, located on the island of Gozo in the Malta-Sicily Channel within the central Mediterranean region, is ideally located to study the primary sources of atmospheric pollution. A total of 10 years of data have been accumulated from the reactive gas and greenhouse gas detectors and the aerosol analyzers found at this Global Atmosphere Watch (GAW) regional station. The data has been evaluated, resulting in trends in emissions from shipping recorded within the same region coming to the fore. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The research also shows that a slow downward trend in SOx and NOx emissions observed. Saliba et al (2021) analyzed the influence of the COVID-19 on maritime transportation modes and air quality. Weng et al (2020) estimated emissions of ships with Yangtze River estuary AIS data with high precision using the STEAM model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research also shows that a slow downward trend in SOx and NOx emissions observed. Saliba et al (2021) analyzed the influence of the COVID-19 on maritime transportation modes and air quality. Weng et al (2020) estimated emissions of ships with Yangtze River estuary AIS data with high precision using the STEAM model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, a comparative analysis of various emissions inventories over Europe for 2008, showed that shipping emissions of NOX and SO2 account respectively for 16% and 11% of the total emissions while highlighting significant differences in the emissions distribution over the Mediterranean [15]. A recent study of the emissions around the Malta-Sicily Channel during the 2020 COVID-19 pandemic restrictions showed that shipping volumes remained the same, explaining the nearly constant air pollution levels measured at a monitoring station within the Malta Channel region [16].…”
Section: Introductionmentioning
confidence: 99%
“…While 70% of global shipping industry atmospheric emissions occur within 400 km of the coast, the impact of ship emissions extends to air quality degradation in coastal regions and harbor towns. The anticipated global ship emissions are forecasted to result in 60,000 premature deaths annually, with the most signi cant consequences concentrated near European, South Asian coastlines, and East Asian areas 7 .…”
Section: Introductionmentioning
confidence: 99%